Sintesis Nanopartikel Poly(NIPAM) Polimer untuk Pemurnian Enzim Protease dengan Teknik Afinitas Presipitasi - Munir Mukhlisin; Risky Rivaldy; Syaubari Syaubari; Muhammad Faisal (Jurnal Inovasi Ramah Lingkungan, 2020)
Currently, the biospecific affinity method for separation has gain attention and is continuously being developed. Precipitation affinity techniques continue to be developed because of it’s simplicity economic value without reducing the purity of the product and the recoverable polymer can be reused And easy to scale-up. The polymer used for the precipitation affinity has a ligand group that can work specifically therefore named "smart polymer". The hydrophilic polymer and the soluble liquid are altered to become hydrophobic and insoluble by changing the pH, temperature, ionic strength, or reagent. The research is used specific ligand for soluble polymers conducted in two stages and tested for enzyme purification.  NIPAM and AIBN are fixed variable for NIPAM polymer synthesis the first stage. The second stage is PABA conjugation where synthesis NIPAM in conjugated with PABA ligands. At this stage, the characterization of PABA is the dependable variable. Dry weight of carboxylated poly(NIPAM) is 91,3%, carboxylated poly(NIPAM)-co MPA 0,4 is 90,4%, carboxylated poly(NIPAM)-co MPA 0,6 is 88,9%. After characterization using SEM, the morphological structure of poly(NIPAM) has a relatively smoother surface. Meanwhile, FTIR characterize obvious changes in weak spectrum 3300-2500 cm . This is due the presence of carboxyl groups characterized in poly(NIPAM). Spectrophotometer tests obtained LCST conditions of 40 -1 C. Conjugation of PABA in poly(NIPAM)-co MPA 0,6 with 50 mg of PABA has better conjugate efficiency with a conjugate yield percentage of 52,6%. o